Pendampingan Restorasi Kegiatan Keagamaan Masyarakat Desa Tertinggal Berbasis Masjid - Moh. Muhyiddin; Ernawati; Sunanul Baroroh (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
Currently, there are no religious activities at the mosque in the Gendono sub-village. This results in a lack of knowledge about the religion of the residents of the Gendono sub-village. Seeing this, the dedication of mosque-based religious activity restoration aims to reactivate the activities of learning to recite the Qur'an and fiqh studies for children and adolescents, as well as increase the ability of teaching cadres to have a qualified capacity for religious material. The method used is Service Learning (SL), which means that in community service, the service team also carries out activities together with the community, but not specifically related to certain teaching. The results obtained are First, there are religious activities at the Gendono Mosque which are attended by teenagers and the community of Gendono sub-village. Second, there is a qualified successor to religious studies in the mosque so that it can be useful to fill the void of mosque activities and increase the religious ability of the Gendono sub-village community.